Development of a nature-based solution for mitigation of Pacific oyster summer mortality: use of the intertidal zone to improve resilience to environmental stressors - Mackenzie, Clara L.; Raap, Monique R.; Leduc, Sarah; Walker, Chen Yin V.; Green, Timothy J.; Kim, Eliah; Montgomery, Emaline M.; Gray, Sierra L. M.; Long, Amy; Pearce, Christopher M. (Frontiers in Marine Science, 2024)
In recent years, Pacific oyster growers in British Columbia (BC), Canada have experienced devastating losses due to summer mortality syndrome. While anecdotal evidence suggests that intertidally-grown oysters may fare better during mass mortality events than deep-water counterparts, there remains a lack of research examining how different culture conditions may influence severity. To address this, we compared growth, condition, histopathology, reproductive status, and survival between intertidally- and deep-water-cultured oysters over 2 years at three oyster farms in Baynes Sound (BC). A reciprocal transplant was carried out after 1 year to test the use of the intertidal as a mechanism for promotion of physiological resilience prior to deep-water deployment. Field trial results showed significantly higher final survival in oysters transferred from the intertidal to deep water (83.5%) compared to those maintained in deep water (63.6%), but only at one farm, likely as a consequence of varying physical and/or biological characteristics associated with particular farm locations. Histopathology showed little role of disease with regards to varying survival among treatments, though higher occurrence of Viral Gametocytic Hypertrophy was observed in Year 1 oysters under deep-water (62.2%) versus intertidal (37.8%) conditions. Additionally, after 2 years, there was no significant difference in oyster size nor condition index between oysters transplanted from the intertidal to deep water and those solely cultured in deep water. A laboratory-challenge experiment determined significantly different survival curves of Year 1 intertidally- and deep-water-cultured oysters under immersion/emersion and warming conditions, with final survival of 88% and 64%, respectively, under conditions of high temperature (25°C) and immersion. Likewise, Year 2 (i.e. post-transfer) intertidally- and deep-water-cultured oysters showed significantly different survival curves under laboratory-based Vibrio challenge conditions (16°C) with final survival of 63% and 34%, respectively. Results suggest that partial culture in the intertidal at some farms may be an effective method for conferring resilience to summer mortality in Pacific oysters.